1967
DOI: 10.1111/j.1151-2916.1967.tb15078.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow Properties of Aqueous Suspensions Containing Kaolins of Varying Degrees of Crystallinity

Abstract: The influence of varying degrees of crystal perfection of several Georgia kaolins on the flow properties of aqueous systems containing these clays was studied. The fractionated clay samples were characterized with respect to clay mineral composition, crystallinity, surface area, and cation-exchange capacity. In general, results indicated that dilatant and associated properties were controlled by the degree of crystal perfection whereas the viscous and plastic properties, at a given water content, were usually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1969
1969
1999
1999

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In order to place the present work in perspective, some of the general conclusions reported by these investigators should be considered. Ormsby and Marcus (1967) found several types of rheological behavior, including Newtonian flow, dilatancy, pseudo-plasticity, and thixotropy; also, they found that for non-dilatant systems, increases in the viscosity of different particle size fractions of a single clay correlated with increased surface area, cation exchange capacity, and crystallinity, while dilatancy occurred in some fractions of intermediate particle size and was especially pronounced in certain fractions of high crystalline clays. They conclude that (i) particle size is of primary importance in controlling viscous and plastic properties, (ii) crystallinity does not generally correlate with flow properties, and (iii) the extent of dilatancy may be qualitatively correlated with the degree of crystallinity when the dilatancy is pronounced.…”
Section: Interpretation and Discussionmentioning
confidence: 97%
“…In order to place the present work in perspective, some of the general conclusions reported by these investigators should be considered. Ormsby and Marcus (1967) found several types of rheological behavior, including Newtonian flow, dilatancy, pseudo-plasticity, and thixotropy; also, they found that for non-dilatant systems, increases in the viscosity of different particle size fractions of a single clay correlated with increased surface area, cation exchange capacity, and crystallinity, while dilatancy occurred in some fractions of intermediate particle size and was especially pronounced in certain fractions of high crystalline clays. They conclude that (i) particle size is of primary importance in controlling viscous and plastic properties, (ii) crystallinity does not generally correlate with flow properties, and (iii) the extent of dilatancy may be qualitatively correlated with the degree of crystallinity when the dilatancy is pronounced.…”
Section: Interpretation and Discussionmentioning
confidence: 97%
“…In recent years, many methods have been suggested to measure cohesiveness quantitatively (Richards, 1966;Jones, 1968a). These include, among others, the split-plate method (Dawes, 1952;Eisner et al, 1960;Shotton and Harb, 1966), tilting cone and tilting plate methods (Cremer et at., 1952;Batel, 1959;Patat and Schmid, 1960;Zimon, 1962;Lowes and Perry, 1965), the sandwich method (Nash et al, 1965;Wjlcox, 1968, 1969), and methods based onrotationalviscometry (Bernarie, 1961 ;Taneya,1963Taneya, ,1965Taneya, ,1969Kunoand Kurihara, 1965;Rutgers, 1966;Cheng and Farley, 1966;Kuno and Senna, 1967;Harwood and Pilpel, 1968a). However, the most satisfactorytheoretically and practically is the shear cell method (Jenike, 1961(Jenike, , 1964(Jenike, , 1965Jenike et al, 1960;Pilpel, 1969a, b).…”
Section: B Cohesion and Tensile Strengthmentioning
confidence: 99%
“…Anderson and Fitzgerald (1967) reported the effects obtained when peptizing or flocculating agents were incorporated into these mixtures. Ormsby and Marcus (1967) showed the influence of the degree of kaolin crystallinity on flow properties. Neumann and Sansom (1970) used Laponite clay (a synthetic inorganic gelling agent for aqueous solutions of polar organic compounds) to prepare dispersions which were insensitive to temperature variations and which were between pseudoplastic and Bingham fluids.…”
Section: Suspensions and Suspending Agentsmentioning
confidence: 99%